The characteristics and mechanisms of carbon finance development on green economic efficiency: an empirical analysis based on endogenous economic growth model - Chen, Yiru; Ma, Guangcheng (Frontiers in Environmental Science, 2024)
In this paper, I explore the impact mechanisms and characteristics of carbon finance on economic sustainability. The results indicate that green total factor productivity has a spatial spillover effect and there are two mediators between carbon finance and green total factor productivity, including technological progress and the increase in technology market turnover. My findings can provide policy implications for sustainable economic development, environmental protection, and resource conservation. Different from previous academic research to study the relationship between carbon finance and green total factor productivity from the theoretical aspect, this paper studies the relationship between carbon finance and green total factor productivity from the empirical aspect and applies spatial econometric models to analyze spatial heterogeneity by using the Romer Endogenous Economic Growth Model. In addition, early scholars were more interested in green finance rather than carbon finance, and just viewed carbon finance as an indicator to construct a green finance index This paper provides suggestions for environmental protections, carbon finance development, and the development of green total factor productivity through data analysis.